KEDUDUKAN DEWA GANESA DALAM THEOLOGI HINDU - Luh Wantari; Widya Gunawan (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
In the concept of Hindu theology Dewa Ganesha has a very important role, Especially in Hindu society in bali. In the belief of the Hindu community in Bali, lord Ganesha is believed to be a god of knowledge and intelligence, a guardian deity, a god of disaster, and a god of wisdom. Lord Ganesha is one of the manifestations or manifestations of God Almighty. He is the first son of lord Shiva and Dewi Parwati. The worship of lord Ganesha is of course to be able to get protection and be kept away from all disasters, the worship of lord Ganesha also aims to gain intelligence and knowledge because this god Ganesha is also a god of intelligence. As the god of Ganesha protection, many are worshiped in Bali, which is manifested by Hindus in the form of a statue of lord Ganesha placed in the yard of a house near the entrance, the purpose of course is to protect the entire contents of the house and family from being exposed to danger. Lord Ganesha was also revered in the implementation of the Rsi Gana mecaru ceremony, as a God who expels all negative influences.